A thermal control surface for the Solar Orbiter. (December 2015) - Doherty, Kevin A.J.; Carton, James G.; Norman, Andrew; McCaul, Terry; Twomey, Barry; Stanton, Kenneth T.
Abstract: A high-absorptivity/high-emissivity (flat absorber) bone char-based thermal control surface known as SolarBlack has been developed for use on rigid and flexible metallic substrates, including titanium, aluminium, copper, stainless steel, Inconel and magnesium alloys. This work describes the thermo-optical properties, stability, and qualification of this surface for use on the European Space Agency's Solar Orbiter mission. SolarBlack is deposited using a proprietry coating technique known as CoBlast and currently stands as the baseline coating for the spacecraft's front surface heat-shield, which is composed of 50 µm titanium foils (1.3×0.3 m) that have been constructed to cover the 3.1×2.4 m 2 shield. The heat shield makes use of the material's highly stable ratio of solar absorptance to near-normal thermal emissivity ( α s / ε N ) as well as its low electrical resistivity to regulate both temperature and electrostatic dissipation in service. SolarBlack also currently stands as the baseline surface for the High-gain and Medium-gain antennae as well as a number of other components on the spacecraft. The thermo-optical stability of SolarBlack was determined using the STAR Facility space environment simulator in ESTEC., Material characterisation was carried out using: SEM, UV/Vis/NIR spectrometry, and IR emissometry. The coating performance was verified on the Structural Thermal Model using ESA׳s Large Space Simulator. Highlights: A flat absorber surface, SolarBlack, has been developed for ESA׳s Solar Orbiter. Adhesion, outgassing, electrical, and thermo-optical measurements were undertaken. The material has been qualified using the STAR facility in ESTEC. SolarBlack is now the baseline thermal control coating for the SolO heatshield.